Inclusión de harina de nacedero y su efecto sobre los parámetros productivos y bienestar animal en cerdos en fase de engorde - Párraga Carranza, Geovanny Baldemar (2022)
The objective of this research was to evaluate the inclusion of different levels of nursery meal (Trichanthera gigantea) and its effect on production parameters and animal welfare in the diet of fattening pigs. Each female pig in the growth phase of the Landrace x Pietrain cross was recently used as an experimental unit distributed in 4 treatments and 6 repetitions, giving a total of 24 observational units. Four treatments were used with levels of 0, 2, 4 and 6% nursery meal. The need for measurable responses to the effect of treatments is carried by an analysis of variance, using Tukey's 5% test. The data was analyzed in the statistical package InfoStat (2020). Finally, the results obtained were tabulated and graphed according to the contribution they presented to the investigation through the use of Microsoft Excel 2016. As results, it was obtained that there is no statistical difference (p>0.05) in the productive parameters in the weeks of treatment, however, although the feed conversion was not significant, treatment 3 (birth meal at 6%) showed the highest efficiency of this with a value of 2.04, likewise this treatment failed the highest profitability with $0.40 for every dollar invested. In conclusion, the inclusion of different levels (2%, 4% and 6%) of (Trichanthera gigantea) meal in the daily diet of pigs in the fattening phase generates statistically similar productive alterations to the control treatment.